Factors Influencing the Implementation of Foreign Innovations in Organization and Management of Health Service Delivery in China: A Systematic Review - Wang, Wenxing; van Wijngaarden, Jeroen; Wang, Hujie; Buljac-Samardzic, Martina; Yuan, Shasha; van de Klundert, Joris (Frontiers in Health Services, 2021)
Background: China has been encouraged to learn from international innovations in the organization and management of health service delivery to achieve the national health reform objectives. However, the success and effectiveness of implementing innovations is affected by the interactions of innovations with the Chinese context. Our aim is to synthesize evidence on factors influencing the implementation of non-Chinese innovations in organization and management of health service delivery in mainland China. Methods: A systematic review was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We searched seven databases for peer-reviewed articles published between 2009 and 2020. Data were analyzed and combined to generate a list of factors influencing the implementation of foreign innovations in China. The factors were classified in the categories context, system, organization, innovation, users, resources, and implementation process. Results: The 110 studies meeting the inclusion criteria revealed 33 factors. Most supported by evidence is the factor integration in organizational policies, followed by the factors motivation & incentives and human resources. Some factors (e.g., governmental policies & regulations) were mentioned in multiple studies with little or no evidence. Conclusion: Evidence on factors influencing the implementation of foreign innovations in organization and management of health service delivery is scarce and of limited quality. Although many factors identified in this review have also been reported in reviews primarily considering Western literature, this review suggests that extrinsic motivation, financial incentives, governmental and organizational policies & regulations are more important while decentralization was found to be less important in China compare to Western countries. In addition, introducing innovations in rural China seems more challenging than in urban China, because of a lack of human resources and the more traditional rural culture.